Studies on leaf senescence of super-highyield rice at flowing and grain formation stage - WENG Xiao-yan; LU Qing; ZHENG Bing-song; JIANG De-an (浙江大学学报. 农业与生命科学版)
Flag leaf senescence of super-highyield rice—Peiai 64s/E32 and conventional rice Zhenong 952 after heading was studied with soil culture. The results indicate that photosynthetic rate decreased in the flag leaf after flowering. There is close relation between photosynthetic rate and content of chlorophyll in the flag leaf. In the meanwhile, the activities of superoxide dismutase (SOD) decreased and the content of malondialdehyde (MDA) increased. Comparing with Zhenong 952, the senescence of flag leaf was speeded up during late growing period of Peiai 64s/E32.